Who is hurt by discrimination? - Birthe Larsen; Gisela Waisman (Copenhagen Business School (CBS), Department of Economics, 2007)
The eects of discrimination of immigrants on the labour market are studied within a search and wage-bargaining setting including a risk of losing skills during the experience of unemployment. The negative eects of discrimination in the form of higher unemployment and lower wages spread to all workers, immigrants and natives, in all sectors of the economy. The eect is stronger for immigrants, but natives suer as well. An increase in the share of immigrants in the economy exacerbates the problem of discrimination
hdl:10398/7634
Keywords: G10; 330